Long-run validity of purchasing power parity and rank tests for cointegration for Central Asian countries - Liew, Venus Khim-Sen; Chia, Ricky Chee-Jiun; Ling, Tai-Hu (Routledge, 2010)
This study finds that Purchasing Power Parity (PPP) holds in the long-run for Azerbaijan, Kazakhstan and Kyrgyzstan, based on Breitung’s (2001) rank tests for cointegration. Results from further analysis indicates that nominal exchange rates and relative prices are nonlinearly interrelated. Trade barriers, transportation costs and government intervention in the pricing system in these countries may have resulted in the establishment of the above-mentioned nonlinear relationship.